The influence of arts engagement on the mental health of isolated college students during the COVID-19 outbreak in China - Yanying Chen; Xue Zeng; Lijian Tao; Junxiang Chen; Junxiang Chen; Yuhui Wang (Frontiers Media S.A., 2022)
ObjectivesThe COVID-19 pandemic significantly impacted the mental health of college students. This study aimed to investigate the buffering effect of arts engagement on anxiety and resilience in college students during the COVID-19 pandemic.Study designA cross-sectional study.MethodsThe data were collected via an online survey during a wave of SARS-CoV-2 infections in Shanghai (March 15 to April 15, 2022). In total, 2,453 college students throughout China reported general anxiety symptom levels (according to the GAD-7), resilience (according to the Connor-Davidson Resilience Scale), frequency of receptive arts engagement in the previous year, exposure to risk situations, and behavioral changes due to the pandemic.ResultsDuring the current stage of the pandemic, 43.7% of college students suffered from varying degrees of anxiety, and 2.6% showed severe anxiety. Gender and learning stage were not associated with anxiety. Hierarchical regression analysis showed that the decision to return to academic institution, the degree of exposure to COVID-19, and the frequency of accepting art participation and resilience could significantly predict the anxiety level of college students. Gender, study stage, behavioral changes arising from COVID-19, and exposure to COVID-19 significantly predict the resilience level of college students. There was an association between high frequency music activities, reading activities and low anxiety level (p < 0.001). There was an association between high frequency digital art, music activities, reading and high resilience (p < 0.01).ConclusionsArts engagement appears to help students cope with mental health problems and those at risk. Policymakers should encourage college students to participate in art activities, especially in the context of social distancing.